SMOKING CONTROL MISCELLANY (Tufts Archival Research Center, 2007)
Marginalia; Clippings from newspapers and magazines containing stores relevant to the tobacco industry. Includes clippings on secondhand smoke, lobbying and workplace smoking bans among others.